Pengaruh Entrepreneurship Education, Entrepreneurial Motivation Terhadap Entrepreneurial Intention Dengan Entrepreneurial Self-Efficacy Sebagai Variabel Intervening Pada Mahasiswa Manajemen Universitas Islam Malang - Arie Andini, Galuh Mayang; Farida, Eka; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The main objective of this research is to determine how entrepreneurship education, entrepreneurial motivation affects entrepreneurial intention with entrepreneurial self-efficacy in the role of intervening variable. The research population in this study were students of the management study program at the Islamic University of Malang. This research used a probability sampling technique so that 100 respondents were determined. One way to analyze data is to use quantitative descriptive methods. The research used a quantitative approach with analysis throught the use of SmartPLS data processing. The findings from this research are that entrepreneurship education and entrepreneurial motivation have a significant effect on entrepreneurial intention, entrepreneurial self-efficacy has a significant effect on entrepreneurial intention, entrepreneurship education and entrepreneurial motivation have a significant effect on entrepreneurial self-efficacy. Entrepreneurship education has a significant effect on entrepreneurial intention through entrepreneurial self-efficacy as an intervening variable, and entrepreneurial motivation has a significant effect on entrepreneurial intention through entrepreneurial self-efficacy as an intervening variable.  Keywords: Entrepreneurship Education, Entrepreneurial Motivation, Entrepreneurial Intention, and Entrepreneurial Self-Efficacy